EFEKTIVITAS PEMBELAJARAN KUTUBUS SITTAH TERHADAP PEMAHAMAN HADITS SHAHIH BAGI SANTRI DARUS SUNNAH CIPUTAT - Yokha Latief Ramadhan (CV. ADIBA AISHA AMIRA, 2023)
Islamic boarding schools are Islamic educational and religious institutions, most of which are taught classically. Among these are the Halaqah and Sorogan methods, in which kiyai teaches students based on books written in Arabic by great scholars since the Middle Ages. The Kutubus Sittah is a book that is the subject of study in the Darus Sunnah pesantren. The Kutubus Sittah includes the books of Sahih Al-Bukhari, Muslim, Sunan Abu Dawud, At-Tirmidhi, An-Nasa'i, and Ibn Majah. Through the Mudzakarah and the halaqah methods, students at the Darus Sunnah Islamic Boarding School can understand authentic hadiths. In this study, researchers used qualitative methods and interviews as a medium to obtain information about the problems found for this study. The purpose of this research is to see how effective the learning of Kutubus Sittah is on students' understanding of authentic hadith.